PENGARUH PEMBERIAN KULIT BUAH KOPI FERMENTASI TERHADAP PERFORMANS, BOBOT HATI, PANJANG DAN PERSENTASE BOBOT USUS HALUS AYAM BROILER - Sitorus, Tunggul Ferry; Telambanua, Apriori Pastra (LPPM Universitas HKBP Nommensen, 2021)
The skin of the coffee fruit is plantation waste that can be used as animal feed because it is available in large quantities and contains quite good food substances; it's just that because it contains several anti-nutritional substances, it is necessary to pre-treat fermentation to reduce the anti-nutritional content and increase its nutritional value. This study aims to examine the effect of giving the skin of coffee beans fermented with tempeh yeast in rations on performance, liver weight, length and percentage of small intestine weight of broiler chickens aged 1 - 5 weeks. This study used the experimental method CRD (completely randomized design) with 5 treatments (P0 = control; P1 = 5%; P2 = 10%; P3 = 15%; and P4 = 20%) and each treatment had 4 replications. The results showed that the fermented coffee pods had a very significant effect (P <0.01) on ration consumption, body weight gain, and ration conversion; but had no significant effect (P> 0.05) on liver weight, length and percentage of small intestine weight.